2008
DOI: 10.1016/j.ejphar.2007.11.047
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral effects of amphetamine in streptozotocin-treated rats

Abstract: Experimentally-induced diabetes can modify the behavioral and neurochemical effects of drugs acting on dopamine systems, possibly through insulin-related regulation of dopamine transporter activity. In this study, several behavioral procedures were used to examine possible changes in sensitivity to amphetamine and other drugs in rats rendered diabetic by a single injection of streptozotocin. Conditioned place preference developed to food (Froot Loops ® ) in both control and diabetic rats, demonstrating that co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…STZ treatment has been shown to decrease D2 receptor sensitivity in behavioral assays assessing catalepsy, yawning, and locomotor activity (Sevak et al, 2005, 2007); although no change in sensitivity of D2 receptors to food reward have been found (Sevak et al, 2008). Studies evaluating the rewarding effects of amphetamine in STZ-treated rats have produced mixed results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…STZ treatment has been shown to decrease D2 receptor sensitivity in behavioral assays assessing catalepsy, yawning, and locomotor activity (Sevak et al, 2005, 2007); although no change in sensitivity of D2 receptors to food reward have been found (Sevak et al, 2008). Studies evaluating the rewarding effects of amphetamine in STZ-treated rats have produced mixed results.…”
Section: Discussionmentioning
confidence: 99%
“…Studies evaluating the rewarding effects of amphetamine in STZ-treated rats have produced mixed results. For example, Galici et al (2003) demonstrated that STZ-treated rats displayed a reduction in amphetamine IVSA, whereas Sevak et al (2008) found that STZ did not alter place preference produced by amphetamine. These results contrast our finding that STZ-treated rats displayed an increase in the rewarding effects of nicotine.…”
Section: Discussionmentioning
confidence: 99%
“…For example, STZ-treated rats display a decrease in the locomotor activating effects of amphetamine, as well as a decrease in amphetamine intake (Galici et al, 2003b;Sevak et al, 2008), although no change in amphetamine CPP was shown (Sevak et al, 2008). Also, diabetic rats do not display changes in cocaine intake (Galici et al, 2003a) but show a decrease in cocaine-induced CPP .…”
Section: Enhanced Nicotine Reward In Rodent Models Of Diabetesmentioning
confidence: 93%
“…Studies on rats have shown that chronic food restriction inhibits the function of DAT [28]. Williams et al [29] found significantly diminished levels and function of DAT in streptozotocin-induced hypoinsulinemic rats, and Daws et al [30] reported decreased DAT function in diet-induced obese states of brain insulin-resistant rats.…”
Section: Discussionmentioning
confidence: 99%